Evangelism in the Modern Era: Viewed from the Perspective of Kiyai Sadrach - Adhis Mareta; Timotius Sukarna (International Forum of Researchers and Lecturers, 2024)
Evangelism in the modern era faces unique challenges and opportunities, especially in the context of a pluralistic society and digital technology. This article looks at evangelism from the perspective of Kiyai Sadrach, a Javanese Christian figure known for his contextualised and inclusive approach. Through this analysis, it will look at how Kiyai Sadrach's principles can be applied in the modern context to promote relevant and effective evangelism.